Potential Mechanisms and Perspectives in Ischemic Stroke Treatment Using Stem Cell Therapies - Zhou, Guoyang; Wang, Yongjie; Gao, Shiqi; Fu, Xiongjie; Cao, Yang; Peng, Yucong; Zhuang, Jianfeng; Hu, Junwen; Shao, Anwen; Wang, Lin (Frontiers in Cell and Developmental Biology, 2021)
Ischemic stroke (IS) remains one of the major causes of death and disability due to the limited ability of central nervous system cells to regenerate and differentiate. Although several advances have been made in stroke therapies in the last decades, there are only a few approaches available to improve IS outcome. In the acute phase of IS, mechanical thrombectomy and the administration of tissue plasminogen activator have been widely used, while aspirin or clopidogrel represent the main therapy used in the subacute or chronic phase. However, in most cases, stroke patients fail to achieve satisfactory functional recovery under the treatments mentioned above. Recently, cell therapy, especially stem cell therapy, has been considered as a novel and potential therapeutic strategy to improve stroke outcome through mechanisms, including cell differentiation, cell replacement, immunomodulation, neural circuit reconstruction, and protective factor release. Different stem cell types, such as mesenchymal stem cells, marrow mononuclear cells and neural stem cells, have also been considered for stroke therapy. In recent years, many clinical and pre-clinical studies on cell therapy have been carried out and numerous results have shown that cell therapy has bright prospects in the treatment of stroke. However, some cell therapy issues are not yet fully understood, such as its optimal parameters including cell type choice, cell doses, and injection routes, therefore, a closer relationship between basic and clinical research is needed. In this review, the role of cell therapy in stroke treatment and its mechanisms was summarized, as well as the function of different stem-cell types in stroke treatment and the clinical trials using stem cell therapy to cure stroke, to reveal future insights on stroke-related cell therapy and to guide further studies.